Parmenides’ Structure of the Earth - Calenda, Guido (Peitho. Examina Antiqua, 2023)
It is generally accepted that the enigmatic fragment 12 of Parmenides, supplemented by the first part of A.tius II 7.1, represents an unlikely cosmos which comprises alternating spherical crowns of fire and night, surrounding the earth. A comparison of the fragment and A.tius’ text shows that the latter adds nothing substantial to the fragment. Thus, fragment 12 can actually represent the structure of the earth, which consists of a core of fire, is surrounded by the layers of the earth’s crust, into which heat is transmitted from within, and on which the goddess of life dwells.